Effect of different initial low pH conditions on biogas production, composition, and shift in the aceticlastic methanogenic population. (October 2019) - Ali, Salman; Hua, Binbin; Huang, Jinhui Jeanne; Droste, Ronald L.; Zhou, Qixing; Zhao, Weixin; Chen, Lu
Highlights: Methanosaeta outcompeted Methanosarcina at elevated levels of acetate up to 66 mM. At an initial pH of 3.5 in the reactor, methanogens were able to degrade 60% COD. At pH 4.5, after acclimatization, the performance was comparable to neutral pH. Initial low pH was neutralized without any buffering agents. pH of the reactor and CH4 in biogas showed a positive correlation. Abstract: Anaerobic digestion (AD) reactors often encounter low pH inhibition during startup and high organic loading periods. The use of a large amount of NaOH in order to raise and buffer the low pH, is reported to be inhibitory to methanogens. In order to address this problem, we acclimatized aceticlastic methanogens to low pH. Methanogens were successfully acclimatized to initial low pH down to 3.5 in a lengthy, five months, acclimatization period. The aceticlastic methanogen, Methanothrix soehngenii which was 96.3% of the total methanogenic population at pH 4.5 and 86.75% at pH 3.5, demonstrated that they were the most tolerant aceticlastic methanogens to low pH. After acclimatization, methane yield at pH 4.5 was comparable to neutral pH. Methanosaeta maintained its dominance over Methanosarcina at an elevated level of acetate (66 mM), and a negative correlation was observed between them. There was a positive correlation between the CH4 content and pH.